APOE‐ε4 and hippocampal volume in the cognitively healthy elderly: Longitudinal analysis reveals origins of apparent cross‐sectional differences: Neuroimaging / imaging and genetics. (7th December 2020) - Zhang, Linda; Duenas, Eva; Long, Christopher; Navas, Susana; Calero, Miguel; Medina, Miguel; Strange, Bryan A
Abstract: Background: The Apolipoprotein Ε ( APOE ) ε4 allele is associated with increased susceptibility to Alzheimer's disease (AD), but its effects on cognition and brain morphology in cognitively normal (CN) elderly are unclear. Using cross‐sectional and longitudinal data, this study aims to determine whether CN elderly adults with the APOE ε3/ε4 genotype show any differences in cognitive performance and neuroimaging measures. Method: 788 CN elderly men and women (aged 69‐86) were selected from the baseline visit of the Vallecas Project cohort based on genotype ( APOE ε3/ε3 ( n =648), ε3/ε4 ( n =140)). Of these 788 subjects, 230 (aged 69‐75 at baseline; APOE ε3/ε3 ( n =192), ε3/ε4 ( n =38)) stayed in the project for at least 5 years, and were selected for longitudinal analysis. All participants underwent detailed neuropsychological and neurological evaluation, and MRI scanning at 3T. Neuropsychological test scores and neuroimaging measures (grey matter density, white matter diffusivity, global brain and hippocampal volumes (HV)) were analysed. Result: From the cross‐sectional analyses, there was a significant genotype‐by‐age interaction in right HV (F (1, 781) =6.06, p =0.014), with ε3/ε3 homozygotes displaying significantly larger volumes before age 75, but similar sized volumes to ε3/ε4 genotypes after age 75 (Fig. 1). However, for the longitudinal subgroup, neither baseline right HV nor its rate of atrophy over 5 years was significantly different between the two genotypes (Fig. 2). A significant genotype‐by‐number of visits interaction (F (1, 433) =6.18, p =0.013) in baseline right HV was found (Fig. 3). Comparison of neuropsychological test scores and other neuroimaging measures did not reveal any significant effects. Conclusion: We conclude that elderly subjects with APOE ε3/ε4 genotype who stay cognitively normal throughout a 5‐year study duration are not cognitively nor morphologically distinct from those with APOE ε3/ε3 genotype, most likely due to a survival effect.